A provably stable numerical method for the anisotropic diffusion equation in confined magnetic fields - Dean Muir; Kenneth Duru; Matthew Hole; Stuart Hudson (Computer Physics Communications, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Integrating Biophysical, Socio-Economic and Governance Principles Into Marine Reserve Design and Management in Mexico: From Theory to Practice - Magdalena Précoma-de la Mora; Nathan J. Bennett; Stuart Fulton; Adrian Munguia-Vega; Cristina Lasch-Thaler; Mariana Walther-Mendoza; José Alberto Zepeda-Domínguez; Elena Marie Finkbeiner; Alison L. Green; Alvin Suárez; Amy Hudson Weaver; Ana Luisa R. Figueroa Carranza; et al. (Frontiers in Marine Science, 2021)
Marine conservation design and fisheries management are increasingly integrating biophysical, socio-economic and governance considerations. Integrative approaches are adopted to achieve more effective, equitable, inclusive, and robust marine policies and practices. This paper describes a participatory process to co-produce biophysical, socio-economic, and governance principles to guide the design and management of marine reserves in three regions of Mexico: the Pacific region of the Baja California Peninsula, the Gulf of California, and the Mexican Caribbean. The process of co-producing the principles included convening a coordination team, reviewing the science, convening multi-stakeholder workshops, developing and communicating the principles with key practitioners and policy makers, and supporting uptake and application to policy and practice. Biophysical principles were related to: habitat representation and risk spreading; protecting critical, special and unique areas; incorporating connectivity; allowing time for recovery; adapting to changes in climate and ocean chemistry; and considering threats and opportunities. Socio-economic principles focused on: integrating the social context, local aspirations, and human-environment interactions; considering economic and non-economic uses, promoting an equitable distribution of costs and benefits, and respecting and maintaining cultural identity and diversity. Governance principles prioritized establishing and ensuring legitimacy and institutional continuity; implementing collaborative and adaptive management; and, promoting effective management. The paper also examines early efforts to implement the principles, next steps to promote further uptake and application in Mexico, and lessons learned from the process. Thus it provides insights into a practical process and a set of principles that are valuable to inform marine conservation and fisheries management processes elsewhere.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Using Modern Conservation Tools for Innovative Management of Coral Reefs: The MANACO Consortium - Oliver Selmoni; Gaël Lecellier; Lara Ainley; Antoine Collin; Raimana Doucet; Vaimiti Dubousquet; Hudson Feremaito; Edouard Ito Waia; Stuart Kininmonth; Hélène Magalon; Siola’a Malimali; Ateliana Maugateau; et al. (Frontiers in Marine Science, 2020)

Untapped Potential of Citizen Science in Mexican Small-Scale Fisheries - Stuart Fulton; Catalina López-Sagástegui; Amy Hudson Weaver; Fernanda Fitzmaurice-Cahluni; Carlos Galindo; Francisco Fernández-Rivera Melo; Silvia Yee; María Belén Ojeda-Villegas; David Antonio Fuentes; Elizabeth Torres-Bahena (Frontiers in Marine Science, 2019)

Holocene river development and environmental change in Upper Wharfedale, Yorkshire Dales, England - Andy J. Howard; Mark G. Macklin; Stuart Black; Karen A. Hudson-Edwards (Journal of Quaternary Science, 2000)